Analisisi Penerapan Akuntansi Manajemen Lingkungan di PT. PINDAD (Persero) - Nilna Kumalawati; Rahma Nazila Muhammad (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study aims to analyze the application of environmental accounting by PT. PINDAD (Persero) in terms of disclosure and reporting on physical and monetary environmental information in 2019 on the management of hazardous wastes. This research is qualitative research with interviews as primary data and company estimate report as secondary data. The data analysis technique used is the Miles and Huberman model data techniques. From the results of this study can be drawn two conclusions based on two different aspects. From the monetary aspect it is known that the environmental recording and disclosure of PT. PINDAD (Persero) has not implemented an environmental cost quality model. While from the physical aspect, environmental recording and disclosure of PT. PINDAD (Persero) is prepare in accordance with the environmental management performance summary document (Permen LH RI No. 3 Tahun 2014). But the physical data of the input material used has not been recorded and revealed in full.